Lewis Acid-Catalyzed Cyanomethylation of α,β-Unsaturated Keto Esters and Activated Ketones Using Vinyl Azide as an Acetonitrile Equivalent - Zhang, Xudong; Yang, Min; Xiao, Jian; Chen, Bin; Xu, Minghui Hui; Wang, Bin-Qin; Hu, Ping; Cao, Peng (Synlett, 2025)
Lewis acid-catalyzed cyanomethylation reactions of α,β-unsaturated ketoesters and ketoamides with α-isopropanol vinyl azide were reported. The corresponding cyanoalkylated products were obtained in 40–97% and 45–96% yields, respectively, through 1,4- and 1,2-addition pathways.
Keywords: Cyanomethylation reaction; Ketoester; Ketoamide; Vinyl azide